Light pollution and seabird fledglings: Targeting efforts in rescue programs. Issue 4 (7th March 2017) - Rodríguez, Airam; Moffett, Jennifer; Revoltós, Anna; Wasiak, Paula; McIntosh, Rebecca R.; Sutherland, Duncan R.; Renwick, Leanne; Dann, Peter; Chiaradia, André
ABSTRACT: One of the most critical phases in the life of petrels (Procellariiformes) is at fledging when young birds pass from parental dependence on land to an independent life at sea. To mitigate mortality at this time, rescue programs are implemented near breeding sites around the world, especially for birds grounded by artificial lights. We evaluated the plumage and body condition of short‐tailed shearwater ( Ardenna tenuirostris ) fledglings captured at colonies just before departure in comparison to fledglings washed up on beaches and to fledglings attracted by artificial light along roads. We measured abundance of down, body mass, and body condition index as the standardized residuals of a regression of body mass on size, and employed linear models to test differences on body mass and body condition between locations. Beach‐washed birds were underweight and in poor condition, suggesting their future survival probabilities at sea were low. Birds rescued on roads as a consequence of light attraction had lower body weights and condition indices than fledglings captured at the colony. However, more than 50% of light‐attracted birds had attained similar weights to those of adults, suggesting they have higher probabilities of survival than beach‐washed birds. Water‐logged birds being washed onto beaches is a natural process, but birds grounded by lighting along roads is an increasing anthropogenic threat that requires management. Thus, management and conservation efforts should be directed to protect birds in the colonies and reduce light‐induced mortality, ideally through the strategic reduction of light sources and lateral light spillage. When resources for conservation are limited, rescue programs should focus on rescuing birds from roads rather than beach‐washed birds, which have a lower probability of survival. © 2017 The Wildlife Society. Abstract : Short‐tailed shearwater fledglings rescued on roads as a consequence of light attraction had higher body weights than beach‐washed fledglings on Phillip Island, Australia, and consequently higher probabilities of survival. Management and conservation efforts should be directed to protect birds in the colonies, improve rescue patrols, and reduce light‐induced mortality, ideally through the strategic reduction of light sources and lateral light spillage.